How accurate is the visual estimation of bowel length by endoscopic surgeons? - Mirzaee, Sahar; Golzarand, Mahdieh; Parsaei, Reza; Toolabi, Karamollah; Amirbeigi, Alireza (Frontiers in Surgery, 2022)
Background: Measurement of small bowel length is an essential step in performing bariatric surgery. Surgeons need to measure bowel length in order to create alimentary and biliopancreatic limbs. Inaccurate bowel measurement may affect the outcome of surgery. However, it is not clear how accurate the measurement of bowel length is by surgeons. Methods: Two image quizzes marking certain lengths of jejunum were sent to participants. They were asked to estimate the length of marked bowels in maze quizzes. the Error of estimation, prevalence of significant error (error greater than 30 percent of actual length), and the relationship between different participant characteristics was investigated. Results: A total of 86 participants answered the questionnaire. The mean error of estimation was 4.62 cm (27%). Twenty-eight participants (33%) had significant errors in estimation of bowel length. Conclusion: While there are surgeons that can estimate bowel length with decent accuracy, significant errors in estimation of bowel length are not uncommon among surgeons. Surgeons should consider adopting techniques for accurate measurement of the small intestine.